2016
DOI: 10.1111/asj.12694
|View full text |Cite
|
Sign up to set email alerts
|

Functional insulin‐like factor 3 (INSL3) hormone‐receptor system in the testes and spermatozoa of domestic ruminants and its potential as a predictor of sire fertility

Abstract: Insulin-like factor 3 (INSL3) is essential for fetal testis descent, and has been implicated in the testicular and sperm functions in adult males; however, similar functions in domestic ruminants remain largely unknown. This study investigated the functional INSL3 hormone-receptor system in adult ruminant testes and spermatozoa, and explored its potential to diagnose the fertility of sires. Testes and spermatozoa were obtained from fertile bulls, rams and he-goats, whereas subfertile testes and spermatozoa wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 46 publications
(72 reference statements)
2
24
0
Order By: Relevance
“…( Figure 8B and C). Especially, RXFP2 expression in meiotic and postmeiotic germ cells in goats are fundamentally consistent with our studies in boars [9,35], bulls, and rams [36], as well as other reports in humans [37] and rats [8].…”
Section: Germ Cell Types Expressing Rxfp2 Mrna and Protein In The Matsupporting
confidence: 93%
See 2 more Smart Citations
“…( Figure 8B and C). Especially, RXFP2 expression in meiotic and postmeiotic germ cells in goats are fundamentally consistent with our studies in boars [9,35], bulls, and rams [36], as well as other reports in humans [37] and rats [8].…”
Section: Germ Cell Types Expressing Rxfp2 Mrna and Protein In The Matsupporting
confidence: 93%
“…With the help of immunofluorescence using RXFP2-specific antibody, we found that RXFP2 was expressed in the equatorial segment and midpiece of goat spermatozoa (Figure 10A). Similar findings are also found in bull and ram spermatozoa [36].…”
Section: Expression and Functionality Of Rxfp2 In The Spermatozoasupporting
confidence: 88%
See 1 more Smart Citation
“…Indeed, recent research has investigated the utility of Insl3 as an indicator of mammalian fertility (e.g. in humans: [110]; in bulls: [111]). Insl3 is also critical for the first phase of testicular descent, the transabdominal phase, which occurs during fetal development in rodents; but Insl3 does not appear to be involved in the inguinoscrotal phase which happens in sexually immature or inactive male rodents (reviewed in [112]).…”
Section: Discussionmentioning
confidence: 99%
“…Deparaffinised sections (4 μm) were immunostained with anti‐RXFP2 antibody (5 μg ml −1 ; GTX108235; GeneTex, Alton Parkway Irvine, Ca, USA) or antiserum pre‐absorbed with recombinant RXFP2 endodomain (400 μg ml −1 ; Kato et al., ) followed by peroxidase labelled polymer conjugated to goat anti‐rabbit IgG (Dako, Carpinteria, CA), according to our method (Minagawa et al., ). Anti‐RXFP2 antibody was directed against human RXFP2 endodomain, and its specificity has been described elsewhere (Pitia et al., , ; Sagata et al., ). Signals were visualised using diaminobenzidine (Dako), and the sections were counterstained with haematoxylin and examined under a BX50 Olympus microscope equipped with a CCD camera and Instudio V105 software (Pixera).…”
Section: Methodsmentioning
confidence: 99%